Management of Early Childhood Education Teacher Training to Improve Teaching Competence - Elya Siska Anggraini; Cinta Atmaditia Fitri; Nuraisyah Pasaribu; Reza Ade Tria; Rohmiana Haloho (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Teaching competence is one of the important factors that determine the success of the learning process in early childhood education. Early childhood teachers are required to have good pedagogical, professional, social, and personal competencies in order to provide learning that is appropriate to children's developmental characteristics. One effort that can be made to improve these competencies is through well-planned and systematic teacher training management. This study aims to describe how the management of PAUD teacher training can improve teachers' teaching competence in the learning process. This study used a qualitative approach with descriptive methods. Data collection techniques were conducted through observation, interviews, and documentation. The results show that teacher training management carried out through planning, implementation, and evaluation stages can improve teachers' understanding in designing learning activities, using creative learning methods, and managing classrooms effectively. In addition, training also has a positive impact on improving teacher professionalism in implementing more innovative and enjoyable learning activities for early childhood.